Countering COVID-19 Vaccine Hesitancy in Pregnancy: the “4 Cs” - Shook, Lydia L.; Kishkovich, Thomas P.; Edlow, Andrea G. (American Journal of Perinatology, 2021)
Despite evidence to support the safety and efficacy of COVID-19 vaccination in pregnancy, and clear recommendations from professional organizations and the Centers for Disease Control and Prevention (CDC) for pregnant people to get vaccinated, COVID-19 vaccine hesitancy in pregnancy remains a significant public health problem. The emergence of the highly transmissible B.1.617.2 (Delta) variant among primarily unvaccinated people has exposed the cost of vaccine hesitancy. In this commentary, we explore factors contributing to COVID-19 vaccine hesitancy in pregnancy and potential solutions to overcome them.Key Points
Keywords: COVID-19 vaccination; vaccine hesitancy; pregnancy; maternal immunization